Health workers’ motivation was significantly higher in private hospitals than public hospitals influenced by intrinsic and extrinsic factors in Northwest Ethiopia - Ayichew, Gebremariam; Atnafu, Desta Debalkie; Hussein, Mohammed; Alemu, Ayenew Takele (Frontiers in Public Health, 2025)
BackgroundMotivation of health workers is crucial for providing high-quality healthcare services and improving the performance of health facilities. However, less attention has been given to this aspect of workplace climate in hospital settings, and there is scant evidence on the level of health workers’ motivation on healthcare delivery. Therefore, this study aimed to assess the motivation of health workers and its determinants at public and private hospitals in Bahir Dar City, Northwest Ethiopia.MethodsA facility-based comparative cross-sectional study was conducted from November 3rd to December 4th, 2021. A simple random sampling technique was used to select 472 study participants. Motivational status was measured using the mean of 14 items on a Likert scale. Descriptive statistics were computed to present results using tables and figures. Bi-variable and multivariable logistic regressions were performed to identify factors associated with motivational status. Strength of association was measured using adjusted odds ratios with the corresponding 95% confidence intervals and statistical significance was declared at p-values less than 0.05.ResultsA total of 458 health workers participated in our study the health workers’ motivational status was found to be 56.3% (95% CI: 52–60.7%). A significant difference in motivational status was observed between private (62.3%) and public hospitals (50.4%) (χ2 = 6.532, p = 0.011). Working in private hospitals (AOR = 1.52; 95% CI: 1.03–2.23), good collegial relationships (AOR = 1.61; 95% CI: 1.1–2.32), job satisfaction (AOR = 1.49; 95% CI: 1.02–2.20), a favorable work environment (AOR = 1.56; 95% CI: 1.06–2.30), and educational status (AOR = 0.4; 95% CI: 0.17–0.94) were significantly associated with higher health workers’ motivational status.ConclusionThe motivational status of health workers was significantly higher in private hospitals than in public hospitals. The proportion of motivated health workers was low, which poses challenges in maintaining a regulated health workforce within the health system. Working in private hospitals, job satisfaction, working environment, higher educational status, and collegial relationships were predictors of motivational status. Therefore, public hospitals should promptly implement both intrinsic and extrinsic motivational strategies.